Cambrian trilobites from the Huérmeda Formation (Iberian Chains, north‐east Spain) and the inadequacy of the Marianian Stage. (25th November 2018) - Álvaro, J. Javier; Esteve, Jorge; Gracia, Fernando; Zamora, Samuel
Abstract: A taxonomic study of the trilobites found in the Marianian parastratotype of the Iberian Chains, north‐east Spain, results in the recognition of the new redlichiid Redlichia isuelaensis sp. nov., the ellipsocephalid Lusatiops ribotanus, and the saukiandids Onaraspis garciae sp. nov., Paulaspis tiergaensis gen. et sp. nov. and Luciaspis matiasi gen. et sp. nov. The diagnosis of the new Subfamily Onaraspininae (Saukiandidae) and its genera takes into account distinct differences in the thorax, which is subdivided into prothorax with spinose and/or macropleural tergites and opistothorax with micropleurid segments. Onaraspis geyeri sp. nov. is erected based on material previously described in Jordan, which was assigned to poorly preserved material of Myopsolenites palmeri from Israel. The temporal correlation of Marianian endemic‐dominant trilobites throughout the Variscan tectonostratigraphic units of the Iberian Peninsula is not supported by acritarchs, archaeocyaths or trilobites. Three diachronous horizons have been proposed to mark the base of the Marianian (based on the first occurrence of two trilobite genera and one archaeocyathan assemblage zone) and two diachronous horizons for the top (based on the first and last occurrence of different trilobite genera). As a result, the Cambrian Epoch‐2 Marianian Stage is ill‐defined and rendered invalid for correlation throughout the Iberian Peninsula.